2016
DOI: 10.1021/jacs.6b02115
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Charging Mechanisms of Supercapacitors

Abstract: Supercapacitors (or electric double-layer capacitors) are high-power energy storage devices that store charge at the interface between porous carbon electrodes and an electrolyte solution. These devices are already employed in heavy electric vehicles and electronic devices, and can complement batteries in a more sustainable future. Their widespread application could be facilitated by the development of devices that can store more energy, without compromising their fast charging and discharging times. In situ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
447
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 604 publications
(454 citation statements)
references
References 89 publications
5
447
0
2
Order By: Relevance
“…For the case of initially filled pores, charging purely by co-ion desorption (X = -1) may offer the fastest charging rates at high voltages, though this mechanism has not yet been observed. 21 Kondrat et al have suggested that ideally the carbon pores would be initially empty of ions (ionophobic pores) to facilitate fast charging, 16,24,40 Our measurements on carbons with different pore sizes help to explain previous electrochemical studies of charging dynamics. 1,[41][42][43] For carbons with smaller average pore sizes and fewer mesopores (< 2 nm), the capacitance decreased more rapidly as the current density was increased.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…For the case of initially filled pores, charging purely by co-ion desorption (X = -1) may offer the fastest charging rates at high voltages, though this mechanism has not yet been observed. 21 Kondrat et al have suggested that ideally the carbon pores would be initially empty of ions (ionophobic pores) to facilitate fast charging, 16,24,40 Our measurements on carbons with different pore sizes help to explain previous electrochemical studies of charging dynamics. 1,[41][42][43] For carbons with smaller average pore sizes and fewer mesopores (< 2 nm), the capacitance decreased more rapidly as the current density was increased.…”
mentioning
confidence: 56%
“…21,22 For example, charging often proceeds via the exchange of counter-ions and co-ions (co-ions are defined as having charge of the same sign as the electrode in which they are located), while charging by coion desorption alone is also a possibility. We introduced the charging mechanism parameter, X, to quantify these different processes, with X taking values of +1, 0 and -1, for the extreme cases of charging by counter-ion adsorption, counter-ion -co-ion exchange, and co-ion desorption, respectively, while intermediate X values indicate contributions from more than one mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A fundamental understanding of molecular mechanisms and electrode kinetics is key to the future improvement of the performance of EEIs and the longevity and commercial success of electrochemical technologies. The distribution and adsorption/desorption of counterions on electrode surfaces, and subsequent ion exchange and electron transfer are vital processes that define the complexity of operating EEIs that are currently being studied using in situ and operando characterization as well as high-level computational modeling (4).…”
mentioning
confidence: 99%
“…When it comes to increasing the capacitance, it has been previously shown, both experimentally and computationally, that the interaction between the electrode material and the electrolyte plays a fundamental role in optimizing the adsorption of the ions [18][19][20] . For example, a big step forward was taken with the perception of the pore size effect and the ion desolvation under confinement made by Chmiola et al 21 when analyzing tetraethylammonium tetrafluoroborate (TEA-BF 4 ) in acetonitrile (ACN) using carbide-derived carbons (CDCs).…”
Section: Introductionmentioning
confidence: 99%